A Metal–Organic Framework as a Multiphoton Excitation Regulator for the Activation of Inert C(sp3)−H Bonds and Oxygen. (22nd November 2021) - Ji, Guanfeng; Zhao, Liang; Wei, Jianwei; Cai, Junkai; He, Cheng; Du, Zenggang; Cai, Wei; Duan, Chunying
Abstract: The activation and oxidization of inert C(sp 3 )−H bonds into value‐added chemicals affords attractively economic and ecological benefits as well as central challenge in modern chemistry. Inspired by the natural enzymatic transformation, herein, we report a new multiphoton excitation approach to activate the inert C(sp 3 )−H bonds and oxygen by integrating the photoinduced electron transfer (PET), ligand‐to‐metal charge transfer (LMCT) and hydrogen atom transfer (HAT) events together into one metal‐ organic framework. The well‐modified nicotinamide adenine dinucleotide (NAD + ) mimics oxidized Ce III ‐OEt moieties to generate Ce IV ‐OEt chromophore and its reduced state mimics NAD . via PET. The in situ formed Ce IV ‐OEt moiety triggers a LMCT excitation to form the alkoxy radical EtO ., abstracts a hydrogen atom from the C(sp 3 )−H bond, accompanying the recovery of Ce III ‐OEt and the formation of alkyl radicals. The formed NAD . activates oxygen to regenerate the NAD + for next recycle, wherein, the activated oxygen species interacts with the intermediates for the oxidization functionalization, paving a catalytic avenue for developing scalable and sustainable synthetic strategy. Abstract : Through covalent modification of the nicotinamide adenine dinucleotide mimics and Ce III ‐OEt moieties in a metal–organic framework, a new multiphoton excitation approach was developed. This new strategy enables step‐by‐step triggering of the photoinduced electron transfer, ligand‐to‐metal charge transfer and hydrogen atom transfer processes for activation of inert C(sp 3 )−H bonds and oxygen.